La Teoría de la Educación en la actividad académica española. Análisis de un indicador - García Carrasco, Joaquín; García Del Dujo, Ángel; Barrón Ruiz, Ángela; González Sánchez, Margarita (Teoría de la Educación. Revista Interuniversitaria, 2009)
Analysis of the denomination of the courses and programs offered at a large number of Spanish universities enabled the authors to identify the different types of internal configuration that the field of Theory of Education acquires at the different institutions, together with the multiple thematic focal points of interest for research and teaching at each university. Some of the problems inherent to the programming of course content are also dealt with.